1992
DOI: 10.1590/s0036-46651992000300003
|View full text |Cite
|
Sign up to set email alerts
|

Biological and morphological characteristics of Schistosoma mansoni from Ribeira Valley, State of São Paulo, Brazil: I - susceptibility of Biomphalaria tenagophila snail to sympatric S. mansoni strain

Abstract: In the São Paulo State, Brazil, where the Biomphalaria tenagophila is the intermediate host, the Ribeira Valley is an important endemic schistosomiasis mansoni area. During last eleven years there has been intense control measures focusing on schistosomiasis. The efforts have been concentrated in the municipalities of Pedro de Toledo and Itariri. We determined the susceptibility of B. tenagophila to sympatric strain of S. mansoni, both recently isolated from Itariri field. In 1988, this strain was isolated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
2
0
0
2
Order By: Relevance
“…The laboratory population had a long patent phase -as long as 119 days (17 weeks) for the few individuals that survived infection. This finding is similar to the results reported by FIGUEIREDO et al 6 , who observed a patent phase for B. tenagophila (also from Ana Dias) that lasted 104 days (14.8 weeks). The main implication of a long patent period is the maintenance of an active schistosomiasis focus.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The laboratory population had a long patent phase -as long as 119 days (17 weeks) for the few individuals that survived infection. This finding is similar to the results reported by FIGUEIREDO et al 6 , who observed a patent phase for B. tenagophila (also from Ana Dias) that lasted 104 days (14.8 weeks). The main implication of a long patent period is the maintenance of an active schistosomiasis focus.…”
Section: Discussionsupporting
confidence: 92%
“…The infection rate recorded for the experimental population was 58.8%, very close to the result reported by FIGUEIREDO et al 6 , who found an infection rate of 60.0% for B. tenagophila from Itariri. PARAENSE & CORRÊA 15 also experimentally infected various B. tenagophila populations from 18 different locations in Brazil and found infection rates varying between 0.0% and 91.5%, the latter figure being for a B. tenagophila population that was also from Itariri.…”
Section: Discussionsupporting
confidence: 90%
“…Tabela 1 -Número de casos autóctones de esquistossomose no estado de São Paulo, distribuído por bacia hidrográfica nos períodos de 1981 a 2008 (Zanna, 2010;CVE, 2008. (Figueiredo et al, 1992;Guimarães et al, 2010).…”
Section: Os Caramujos Hospedeiros Intermediários Do Gênerounclassified
“…5%, para B. tenagophila de Itariri, distrito de Ana Dias, exposta a 10 miracídios da linhagem SJ Figueiredo et al (1992). obtiveram taxa de infecção de 60%, quando a exposição A infecção experimental de B. tenagophila de Caraguatatuba do bairro de Indaiá mostrou taxa de infecção de 50% a 73,3% após a exposição à linhagem SJ e 60 a 76,7%, quando a exposição foi pela linhagem SJS.…”
unclassified